Encouraging public transportation to increase active commutation in Manhattan, KS - Singh, Annapurna (Kansas State University, 2018)
Transportation is a means of commutation for goods and people and is also an indicator of socioeconomic status of a community. Recently, there has been much debate and research on the impact of transportation on the health care of a community. Lately, it has been proved that increased dependence of people on cars has led to lack of exercise in their daily life. This lack of exercise has been identified as the root cause of severe cardiovascular ailments like high blood pressure, hypertension and even several types of cancers. As a solution, many planners are now proposing public transit (which forces people to walk to and from transit stations) and other active modes of transport like bikes etc. as alternative transportation options to improve community health and reduce dependence on cars. These options not only help people incorporate exercise in their daily life but a reduction in car usage reduces the demand for parking spaces, traffic congestions, carbon footprints of communities and is fuel efficient. This project based in the City of Manhattan is aimed at suggesting measures to enhance the use of public transit among students at Kansas State University to help incorporate more exercise in their daily lives. The project encompassed an observational study to identify the options currently available for transit and factors which affected transit ridership in the city. The observational study was followed by discussion with a focus group to draw views and opinions. These opinions and views were included in a questionnaire for an online survey to identify areas or measures which were most likely to enhance transit ridership positively and cost effectively. This project provides suggestive guidelines regarding students’ opinion about transit in Manhattan. These suggestions could be used to guide policies and strategies for enhancing transit ridership in the city.
Keywords: Active commutation; transportation; public transit; bus; Manhattan